Beating Barriers to Formative Assessment in a Testing-Oriented Nation - Defianty, Maya; Wilson, Kate (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2024)
AbstractIndonesia has a been a testing-oriented country since its inception. Yet, over the past decade, assessment policies in Indonesia have gradually strengthened their emphasis on formative assessment. In general, Indonesian teachers’ understanding of formative assessment is still relatively modest; in fact, some teachers still consider formative assessment to be challenging, if not impossible. Nevertheless, others have embraced the concept and have managed to overcome the barriers of large classes, limited time, and the long-standing culture of high-stakes testing. This article aims to provide examples of good practice in formative assessment in ELT. We present the results of a multiple case study, involving eight ELT senior high school teachers representing various learning contexts in Indonesia. Drawing on data from interviews and classroom observations, the study revealed that these teachers recognized the barriers in implementing formative assessment deriving from limited time and large classes, yet they were able to overcome these barriers by using teaching modifications and technological tools as solutions to applying formative assessment. This study highlights the pivotal role of teachers’ assessment literacy to enhance and reap the benefits from formative assessment. AbstrakIndonesia telah menjadi negara yang berorientasi pada ujian sejak awal berdirinya. Tetapi, selama dekade terakhir, kebijakan penilaian di Indonesia secara bertahap semakin menekankan pada penilaian formatif. Secara umum, pemahaman guru-guru Indonesia tentang penilaian formatif masih relatif terbatas; faktanya, beberapa guru masih menganggap penilaian formatif sebagai hal yang menantang, bahkan tidak mungkin dilakukan. Meskipun demikian, beberapa guru telah menerima konsep ini dan berhasil mengatasi hambatan seperti kelas yang besar, waktu yang terbatas, dan budaya ujian berisiko tinggi yang telah berlangsung lama. Artikel ini bertujuan untuk memberikan contoh praktik baik dalam penilaian formatif dalam pengajaran Bahasa Inggris. Kami menyajikan hasil studi multi-kasus, yang melibatkan delapan guru Bahasa Inggris sekolah menengah atas yang mewakili berbagai konteks pembelajaran di Indonesia. Berdasarkan data dari wawancara dan observasi kelas, studi ini mengungkapkan bahwa para guru ini menyadari hambatan dalam menerapkan penilaian formatif yang berasal dari waktu yang terbatas dan kelas yang besar, namun mereka mampu mengatasi hambatan tersebut dengan menggunakan modifikasi pengajaran dan alat teknologi sebagai solusi untuk menerapkan penilaian formatif. Studi ini menyoroti peran penting literasi penilaian guru untuk meningkatkan dan memetik manfaat dari penilaian formatif. How to Cite: Defianty, D., Wilson, K. (2024). Beating Barriers to Formative Assessment in a Testing-Oriented Nation. TARBIYA: Journal of Education in Muslim Society, 11(1), 1-12. doi:10.15408/tjems.v11i1. 40391.